Volume of Fluid Simulations of Heat Transfer in Liquid-Liquid Segmented Flows in Microfluidic channel - Bashir, Shazia; Shaukat, Saad; İnç, Mustafa; Bashir, Muhammad; Maqbool, Ayesha; Iqbal, Muhammad Sajid; Afzal, Farkhanda (Springer, 2023)
This study presents the investigations on the effect of heat transfer on droplet formation in T-type microfluidic channel. Mineral oil acts as a continuous phase, and water acts as a dispersed phase. The Volume of Fluid model is used to investigate the formation of droplets of water in oil in the microchannel. The physical properties of both fluids change with an increase in temperature of dispersed phase, of which the dominant properties are viscosities of fluids and interfacial tension. The parameters such as droplet diameter, distance between two consecutive droplets and detachment time were studied with respect to temperature in the range of 300 K to 325 K. These properties are also studied at different flow rate ratios 0.125, 0.25, and 0.5. The distance between two consecutive droplets was found to decrease with the increase in temperature due to the rapid motion of droplets in the temperature zone. The droplet detachment time also decreases, due to the decrease in interfacial forces which hold the droplets in the dispersed phase. The droplet diameter decreases initially with the increase in temperature, but it was observed that after 320 K the diameter of the droplet increases due to the coalescence of two consecutive droplets downstream in the microchannel. This temperature is reported as a limiting condition for thermally controlled water-in-oil microemulsions.
Keywords: T-type microfluidic channel; Volume of Fluid model; Mineral oil; Microchannel